PLGA–PEG–PLGA self-aggregation study via fragment dissipative particle dynamics and quantum determined interaction parameters - Coreno-Cortés, A. A.; Cortés-Cuán, M. A.; Santamaría-Holek, I. (Frontiers in Physics, 2025)
In this work, we used Conductor-like Screening Model for Real Solvents (COSMO-RS) to calculate the parameters that characterize the interactions between molecular segments in a coarse-grained representation of the PLGA–PEG–PLGA mesomolecule. The computed activity coefficients at infinite dilution were then used to obtain the thermodynamic Flory–Huggins interaction parameters, which were subsequently transferred to Dissipative Particle Dynamics simulations. In these simulations, beads interact through repulsive conservative parameters to investigate the self-aggregation of the PLGA–PEG–PLGA triblock copolymer. The parameters were then applied in Dissipative Particle Dynamics (DPD) simulations at varying copolymer concentrations. Self assembling at different concentrations was studied. Transitions from core-shell spherical micelles to onion-like, columnar and lamellar structures were obtained in terms of copolymer concentration, setting the optimal concentration range for different drug loaded vehicles.